Oğuz Eli'nde dini hayat - Erman, Ebru (My University, 2020)
Oğuzeli ilçesinin tarihi M.Ö. 3000’li yıllara kadar dayanmaktadır ve bu bölge Hititler, Asurlar, Medler, Persler, Sasaniler ve Bizans gibi birçok medeniyete ev sahipliği yapmıştır. Araştırmamızda birçok medeniyete ev sahipliği yapmış bu ilçenin dini hayatı ele alınmıştır. Araştırmanın temel hipotezi Oğuzeli İlçesi’nde geleneksel bir dindarlık anlayışının sürdüğü yönündedir. Araştırmanın teorik kısmında nitel dolaylı gözlem tekniklerinden belge tarama yöntemi kullanılırken uygulama kısmında yine dolaylı gözlem tekniklerinden anket ve mülakat kullanılmıştır.

History of Oğuzeli district dates back to B.C 3000s and this region has hosted many civilizations such as the Hittites, Assyrians, Meds, Persians, Sassanids, Byzantines. In our research, the religious life of this district, which has hosted many civilizations, is discussed. The main hypothesis of the research is that a traditional understanding of religiousness continues in Oğuzeli District. While the document scanning method, which is one of the qualitative indirect observation techniques, has been used in the theoretical part of the research, the survey and interview, which is one of the indirect observation techniques, have been used in the application part.
Keywords: Din; Din ve sosyoloji; Dindarlık; Dini Hayat; Dini yaşam; Gelenek; Geleneksel Toplum Oğuzeli; Islam; İslam; Manners and customs; Oğuzeli; Örf ve adetler; Piety; Religion; Religion and sociology; Religious life; Society; Toplum; Tradition; Traditional Society